Self-management of persons living with diabetes mellitus type 2: Experiences of diabetes nurse educators - Coleen O'Brien; Dalena van Rooyen; Esmeralda Ricks (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2020)
Background: The global pandemic of diabetes mellitus type 2 (DM2) is the direct cause of significant health and economic problems for both governments and individuals owing to the high level of morbidity and mortality. South Africa has the second highest incidence of DM2 in sub-Saharan Africa.